2018
DOI: 10.1038/s41467-018-07823-5
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution acoustophoretic 3D cell patterning to construct functional collateral cylindroids for ischemia therapy

Abstract: The fabrication of functional tissues is essential for clinical applications such as disease treatment and drug discovery. Recent studies have revealed that the mechanical environments of tissues, determined by geometric cell patterns, material composition, or mechanical properties, play critical roles in ensuring proper tissue function. Here, we propose an acoustophoretic technique using surface acoustic waves to fabricate therapeutic vascular tissue containing a three-dimensional collateral distribution of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 67 publications
2
117
0
Order By: Relevance
“…Previous studies demonstrated cortical bone-mimicking scaffolds without cancellous bone structure via DLP-based 3D printing (21). However, besides cancellous bone structure, the biological functions of these structures, the key points of tissue reconstruction in vivo, were neglected (22). Thus, a simple model mimicking the primary structure and function of Haversian bone is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated cortical bone-mimicking scaffolds without cancellous bone structure via DLP-based 3D printing (21). However, besides cancellous bone structure, the biological functions of these structures, the key points of tissue reconstruction in vivo, were neglected (22). Thus, a simple model mimicking the primary structure and function of Haversian bone is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This method allowed cell arrays to be preserved for long-term in vitro tissue engineering after removal of the acoustic field. Since 2016, devices have been developed to generate lines of myoblasts for skeletal muscle tissue engineering [45] ( Figure 4A), assemblies of beating cardiomyocytes for cardiac tissue engineering [46,47], levitated sheets of neuroprogenitors for neural tissue engineering [48] ( Figure 4B) and arrays of endothelial cells for neovascularization [49,50] (Figure 4C). These examples use simple geometric arrays to create lines, columns, or sheets, however, in the future it may be possible to create customized tissue architecture by employing more flexible holographic assembly routes [51,52].…”
Section: Acoustic Fieldsmentioning
confidence: 99%
“…(iii) Image of aligned vessels, perfused with fluorescent dextran (green), 1 week after subcutaneous transplantation, scale bar = 200 mm. Reproduced, with permission, from [50]. systems, which can require considerable expense and expertise to operate and maintain, tend to be sold as multifunctional apparatus rather than tailored to particular end-user applications.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…The use of ultrasound to non-invasively pattern cells is of growing interest to tissue engineering, as spatial cues such as relative position, spacing, and density of cells serve as important determinants of cellular behavior [71][72][73]. USWF exposures have been used to pattern a variety of cell types, including fibroblasts, endothelial cells, Schwann cells, and myocytes to produce enhanced collagen gel contraction [74], vascular network formation [75][76][77], and cellular alignment [78][79][80][81], respectively.…”
Section: Acoustic Mechanisms Of Ultrasound-induced Bioeffectsmentioning
confidence: 99%